Liparis cordicallosa (Orchidaceae), a new species from China: Evidence from morphological and molecular analyses - Long, Bo; Jia, Ruo-Su; Zhang, Ze; Xu, Ru-Hua; Yang, Li-Kun; Zhang, Yu; Zhao, Da-Ke (Phytotaxa, 2025)
A new orchid species, Liparis cordicallosa, is described and illustrated from Yunnan Province, China, based on comprehensive morphological and phylogenetic analyses. Morphological information reveals that L. cordicallosa is most similar to L. distans, but can be distinguished by its ovoid pseudobulbs enclosed by two clasping basal foliaceous sheaths, and a thick waxy and oblong lip recurved at the base and deflexed above middle, with a U-shape grooved and heart-shaped callus at its base, and an acuminate rostellum. The phylogenetic analysis using nrITS and plastid matK DNA sequences further supports the distinctiveness of L. cordicallosa as a distinct species, forming an independent lineage sister to L. distans and its allies (99% bootstrap support, 1.00 posterior probability).